Declining rates of sterilisation reversal procedures in western Australian women from 1990 to 2008: the relationship with age, hospital type and government policy changes. Issue 1 (December 2017) - Jama-Alol, Khadra; Bremner, Alexandra; Pereira, Gavin; Stewart, Louise; Malacova, Eva; Moorin, Rachael; Preen, David
Abstract Background Female sterilisation is usually performed on an elective basis at perceived family completion, however, around 1–3% of women who have undergone sterilisation elect to undergo sterilisation reversal (SR) at a later stage. The trends in SR rates in Western Australia (WA), proportions of SR procedures between hospital types (public and private), and the effects of Federal Government policies on these trends are unknown. Methods Using records from statutory state-wide data collections of hospital separations and births, we conducted a retrospective descriptive study of all women aged 15–49 years who underwent a SR procedure during the period 1st January 1990 to 31st December 2008 (n = 1868 procedures). Results From 1991 to 2007 the annual incidence rate of SR procedures per 10, 000 women declined from 47.0 to 3.6. Logistic regression modelling showed that from 1997 to 2001 the odds of women undergoing SR in a private hospital as opposed to all other hospitals were 1.39 times higher (95% CI 1.07–1.81) and 7.51 times higher (95% CI 5.46–10.31) from 2002 to 2008. There were significant decreases in SR rates overall and among different age groups after the Federal Government interventions. Conclusion Rates of SR procedures in WA have declined from 1990 to 2008, particularly following policy changes such as the introduction of private health insurance (PHI) policies. This suggests decisions to undergo SR may be influenced by Federal Government interventions.